2016
DOI: 10.1093/nar/gkw823
|View full text |Cite
|
Sign up to set email alerts
|

Competitive regulation of alternative splicing and alternative polyadenylation by hnRNP H and CstF64 determines acetylcholinesterase isoforms

Abstract: Acetylcholinesterase (AChE), encoded by the ACHE gene, hydrolyzes the neurotransmitter acetylcholine to terminate synaptic transmission. Alternative splicing close to the 3΄ end generates three distinct isoforms of AChET, AChEH and AChER. We found that hnRNP H binds to two specific G-runs in exon 5a of human ACHE and activates the distal alternative 3΄ splice site (ss) between exons 5a and 5b to generate AChET. Specific effect of hnRNP H was corroborated by siRNA-mediated knockdown and artificial tethering of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 60 publications
1
52
0
Order By: Relevance
“…One function of τCstF-64 is to promote polyadenylation at proximal sites over distal sites [25, 65]. More specifically, a recent study demonstrated that CstF-64 cooperates with hnRNP H to regulate acetylcholinesterase isoforms in human neuronal cells [66], suggesting that τCstF-64 might play a similar role. Further, it has been shown that alternative 3′ exons participate in localization of mRNAs within neurons, for example to neural projections [67].…”
Section: Discussionmentioning
confidence: 99%
“…One function of τCstF-64 is to promote polyadenylation at proximal sites over distal sites [25, 65]. More specifically, a recent study demonstrated that CstF-64 cooperates with hnRNP H to regulate acetylcholinesterase isoforms in human neuronal cells [66], suggesting that τCstF-64 might play a similar role. Further, it has been shown that alternative 3′ exons participate in localization of mRNAs within neurons, for example to neural projections [67].…”
Section: Discussionmentioning
confidence: 99%
“…Competition between CstF‐64 and hnRNP H (see Figure ) alters both polyadenylation and splicing in acetylcholinesterase and other transcripts in human neuron‐like cells (Nazim et al, ). Similarly, HuR/Elavl1 competes with CstF‐64 for binding to U‐rich sequences (H. Zhu, Zhou, Hasman, & Lou, ), which may have consequences in neuronal cells (K. Sun et al, ).…”
Section: Abundant Alternative Polyadenylation In the Brain Supports Nmentioning
confidence: 99%
“…First, alternative splicing of a single pre‐mRNA generates three different catalytic subunits called T, H, and R, which share a common N‐terminus and have specific C‐terminal peptides . The mechanisms regulating splicing choices have been partially decrypted . Second, AChE subunits are posttranslationally modified or associated with different peptides.…”
Section: The Origin Of Ache Deficiency In the Synaptic Cleftmentioning
confidence: 99%